Kajian Hubungan Populasi Tanaman dengan Neraca Unsur Hara Nitrogen dan Fosfor pada Sistem Vertikultur Sawi Hijau (Brassica juncea L) dan Kangkung (Ipomea reptana) - I MADE PURNA WIDANA; ANAK AGUNG ISTRI KESUMADEWI; DESAK NYOMAN KASNIARI (Fakultas Pertanian Universitas Udayana, 2016)
Analysis of Relationship Between Crop Density and The Balancing of Both Soil Nitrogenand Phosporus in Verticulture System of Mustard Green (Brassica juncea L) and Kale(Ipomea reptana). The relationship between crops density and the balancing of both soilnitrogen and phosphorus in verticulture system remained to be important issue. A glasshouseexperiment had carried out from October 2014 to March 2015 in order to determine (1) theoptimum population density of both mustard greens (Brassica juncea L) and kale (Ipomeareptana), (2) soil total-N or available-P balance, and (3) the relatiohships between plantspopulations and soil nutrients balance. A split plot experiment under complete block designwas applied to examine the effect of the main plot (crops type i.e. mustard green and kale) andsub plot (crops population i.e 10, 15, 20,25, and 30 crops per planting container 0,12 m2 insize). The results showed that no optimal crops population density had achieved. Themaximum crops population was 30 for both mustard greens and kale. The soil total-N balancewas negative while these was positive for soil available-P balance of P and N negative. Alogarithmic relationships was calculated between soil total-N balance with mustard green,while linier patterns were significant for soil-N balance with kale and available-P balancewith both mustard greens and kale.